2019
DOI: 10.1016/j.ekir.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Assessment of C4d-Positive Renal Transplant Biopsies Without Evidence of Rejection

Abstract: IntroductionImmunohistochemical staining for C4d in peritubular capillaries has been part of antibody-mediated rejection (AbMR) definition in the Banff Classification for Allograft Pathology since 2003. However, it has limited sensitivity and specificity, therefore the clinical significance of C4d-positive biopsies without evidence of rejection (C4d+ WER) is unknown. We investigated the transcript levels of genes associated with AbMR in C4d+ WER biopsies from both ABO-compatible and incompatible renal transpla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 39 publications
0
26
0
1
Order By: Relevance
“…Recently, more practical technologies based on FFPE biopsy analysis are now available, in particular the NanoString nCounter system (NanoString Technologies, Seattle, WA). Several NanoString publications using FFPE transplant specimens identify similar transcript associations with the molecular and histologic phenotypes as those reported in microarray studies 3,4,13‐18,27‐29,29‐33 . Among the advantages of NanoString are (1) a separate core processed at the time of biopsy is not required; (2) transcripts are assessed in the same sample analyzed by light microscopy; and (3) large retrospective and longitudinal analyses of archived samples can be readily performed in the setting of multicenter studies, which will enable retrospective randomization with long‐term survival end points available (Table 1).…”
Section: Current State Of Molecular Transplant Diagnosticsmentioning
confidence: 80%
“…Recently, more practical technologies based on FFPE biopsy analysis are now available, in particular the NanoString nCounter system (NanoString Technologies, Seattle, WA). Several NanoString publications using FFPE transplant specimens identify similar transcript associations with the molecular and histologic phenotypes as those reported in microarray studies 3,4,13‐18,27‐29,29‐33 . Among the advantages of NanoString are (1) a separate core processed at the time of biopsy is not required; (2) transcripts are assessed in the same sample analyzed by light microscopy; and (3) large retrospective and longitudinal analyses of archived samples can be readily performed in the setting of multicenter studies, which will enable retrospective randomization with long‐term survival end points available (Table 1).…”
Section: Current State Of Molecular Transplant Diagnosticsmentioning
confidence: 80%
“…It is also hoped that implementation of molecular diagnostics could help classifying these cases in a more pathogenesis‐driven way, either employing the Molecular Microscope Diagnostic System (MMDx) 25 or the NanoString platform that can be used with formalin‐fixed, paraffin‐embedded tissue, 26 providing greater insight into factors predictive of the biological behavior of MVI without detectable anti‐HLA DSAs, as well as cases with C4d staining without MVI 27 . Current recommendations of the Banff Molecular Diagnostics Working Group in these and other circumstances are detailed in a separate meeting report.…”
Section: Clarification and Updates To The Banff 2017 Classification Rmentioning
confidence: 99%
“…The observation of 'C4d-positive renal transplant biopsies without evidence of rejection' is also associated with uncertainty. Intriguingly, one study performed gene expression analysis and identified patients at higher risk of developing ABMR among these cases [54].…”
Section: Uncertain Pathogenesis For Similar Morphologiesmentioning
confidence: 99%